2002
DOI: 10.1046/j.1365-3156.2002.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of ferrochloroquine against 55 Senegalese isolates of Plasmodium falciparum in comparison with those of standard antimalarial drugs

Abstract: SummaryThe in vitro activities of ferrochloroquine, chloroquine, quinine, mefloquine, halofantrine, amodiaquine, artesunate, atovaquone, cycloguanil and pyrimethamine were evaluated against Plasmodium falciparum isolates from Senegal (Dielmo, Ndiop), using an isotopic micro-drug susceptibility test. The IC 50 values for ferrochloroquine ranged from 0.55 to 28.2 nM and the geometric mean IC 50 for the 55 isolates was 7.9 nM (95% CI, 6.5-9.7 nM). Ferrochloroquine was 35 times more active than chloroquine (35-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
43
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 32 publications
13
43
1
2
Order By: Relevance
“…In all these studies, LM activity was high, with IC 50 s of Ͻ30 nM for more than 95% of isolates (1, 4, 16, 21, 25, 26). In our study, we observed a higher LM IC 50 range, and IC 50 s of Ͼ200 nM for some isolates, findings similar to those of a report from Senegal (27).…”
Section: Discussionsupporting
confidence: 92%
“…In all these studies, LM activity was high, with IC 50 s of Ͻ30 nM for more than 95% of isolates (1, 4, 16, 21, 25, 26). In our study, we observed a higher LM IC 50 range, and IC 50 s of Ͼ200 nM for some isolates, findings similar to those of a report from Senegal (27).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we demonstrated in vitro crossresistance between dihydroartemisinin and mefloquine or lumefantine. The in vitro cross-resistance between lumefantrine and artemisinin derivatives has been observed previously (32). However, no in vitro resistance to both lumefantrine and dihydroartemisinin, monodesethylamodiquine and dihydroartemisinin, or atovaquine and proguanil was demonstrated.…”
Section: Discussionsupporting
confidence: 56%
“…The results of this study seem to indicate a difference in the modes of action of AQ and DAQ, highlighting the crucial role of very low AQ concentrations in the potentiation of DAQ activity. This phenomenon is apparently not unique to AQ and DAQ; similar interactions have been observed recently between chloroquine with its metabolite (15), among diastereomers of the Cinchona alkaloids in vitro (10,34), and between ␤-artemether and lumefantrine (21,24).…”
supporting
confidence: 70%